Prospective Evaluation of the Efficacy of a Food Supplement in Increasing Photoprotection and Improving Selective Markers Related to Skin Photo-Ageing - Corinne Granger; Sonia Aladren; Jesus Delgado; Aurora Garre; Carles Trullas; Yolanda Gilaberte (Adis, Springer Healthcare, 2019)
Abstract Introduction Skin exposure to ultraviolet radiation (UVR) can cause oxidative stress, particularly in the absence of adequate protective measures or in individuals with a sensitive skin type. Most commonly, protection from UVR entails the use of topical sunscreens. Sunscreens, however, have various limitations. The objective of this study was to evaluate the efficacy and tolerability of an oral food supplement containing a combination of actives with mainly antioxidative properties (vitamins A, C, D3, E, selenium, lycopene, lutein, as well as green tea, polypodium and grape extracts) in the context of photoprotection. Methods Photoprotective efficacy was assessed in a 12-week-long, open, prospective and monocentric clinical study with 30 subjects (27 women and 3 men) having a Fitzpatrick skin type I-III and manifesting clinical ageing signs. The study included several visits (14, 28, 56, and 84 days after starting supplement intake), in which photoprotection was evaluated by the measurement of the minimal erythema dose (MED), while the antioxidant capacity of the skin was assessed through ferric reducing antioxidant power (FRAP) and malondialdehyde (MDA) assays. Additionally, several skin parameters (including radiance, elasticity, and moisture) were evaluated. Product evaluation was performed throughout the length of the study by means of a self-assessment questionnaire, and safety was monitored through a self-recording of all observed adverse reactions. Results The MED levels increased significantly compared to baseline throughout the study visits, reaching an increase of + 8.1% at T84, p < 0.001. FRAP results also indicated a significant increase in the antioxidant capacity of the skin compared to baseline (+ 22.7% at T84, p < 0.001), while the MDA assay showed a significant decrease in MDA concentration compared to baseline (− 6.4% at T84, p < 0.001) which, in line with the FRAP results, indicated enhanced antioxidative protection of the skin. All assessed skin parameters, including radiance (+ 36.1% at T84, p < 0.001), gross elasticity (+ 13.2% at T84, p < 0.001), net elasticity (+ 28.0% at T84, p < 0.001), and moisture (+ 13.8% at T84, p < 0.001) were also significantly improved. The product was well tolerated as no adverse events were attributed by the investigators to the use of the product. Additionally, the global score obtained from the self-assessment questionnaires provided overwhelmingly positive feedback from the study subjects. Conclusions The food supplement evaluated in this study was effective and well-tolerated by the subjects, demonstrating a beneficial effect in terms of photoprotection, enhancing the antioxidative status of the skin and improving general skin condition. Trial Registration Retrospectively registered 3rd October 2019, ISRCTN18121679.